2012
DOI: 10.1080/13668803.2012.724220
|View full text |Cite
|
Sign up to set email alerts
|

Working from home: do formal or informal telework arrangements provide better work–family outcomes?

Abstract: Telework arrangements include a suite of options that workplaces provide to meet the growing demand for greater work flexibility and as a strategy to promote work-family balance. However, there has been minimal research comparing formal versus informal telework arrangements, and how they might support employees to manage the competing demands of work and family life. In this paper we examine how formal and informal telework arrangements impact on public sector employees' job satisfaction, time spent on childca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 27 publications
4
83
0
7
Order By: Relevance
“…In another US survey, 78 percent of the respondents say that their supplemental telework is not based on a formal agreement and 21 percent report that they do not get paid for this kind of work (Song 2009). These results are largely supported by surveys and studies in other countries as well (Fenner and Renn 2010;Golden 2012;Natti et al 2011;Towers et al 2006;Troup and Rose 2012). Another very important aspect is the gender dimension of partial telework.…”
Section: Working Hours and Work Schedulesmentioning
confidence: 53%
“…In another US survey, 78 percent of the respondents say that their supplemental telework is not based on a formal agreement and 21 percent report that they do not get paid for this kind of work (Song 2009). These results are largely supported by surveys and studies in other countries as well (Fenner and Renn 2010;Golden 2012;Natti et al 2011;Towers et al 2006;Troup and Rose 2012). Another very important aspect is the gender dimension of partial telework.…”
Section: Working Hours and Work Schedulesmentioning
confidence: 53%
“…Thus, we control for the employment of the spouse (is your spouse (cohabiting partner) currently: working for an employer/working on the family farm or in a family business/self-employed). Fourth, Troup and Rose (2012) found that the sharing of child care duties between spouses importantly shapes work-life balance outcomes. We utilise two measures: which person in your family usually does the following chores:…”
Section: Ijssp 341/2mentioning
confidence: 97%
“…Thus, in our interpretation, autonomy can and should be manageable without the need to extend the temporal and spatial limits of work. In the study by Troup and Rose (2012), the construct used for measuring informal at-home-arrangements includes negotiations with a supervisor and thus excludes work done at home without discussion. In Fenner and Renn (2010), measuring after-hour working is tied to the use of advanced technological tools, which reflects a traditional way of measuring telework before the expansion of IT technologies.…”
Section: Telework and Informal Work At Home: Heterogeneous Concepts Amentioning
confidence: 99%
“…The requirement for organisations in some countries to consider requests from employees to switch to flexible working arrangements has been another key driver for telework adoption. Furthermore, telework popularity has risen as a result of speculations promoted by advocates of flexible working that telework arrangements can modernise workplace practice (Troup and Rose, 2012).…”
Section: Introductionmentioning
confidence: 99%